The Opportunity for Profit to College Student-AthletesAnalysis Study - Ezzeldin R. Aly; Sherin Y. Elmahdy (European Scientific Journal, ESJ, 2024)
A recent study by Romero (2018) suggests that NCAA athletes should receive better compensation. College student-athletes put in much time and energy, but many do not receive adequate pay. High school athletes’ chances of participating in college sports are lower without scholarships. It is time to recognize their value and provide financial support. (NCAA) is a nonprofit organization that regulates collegiate sports, and this study emphasizes the livelihood of collegiate student-athletes and the rules they must follow. Furthermore, the study compares the coach’s salaries with collegiate student-athlete student-athletes to profit from their crafts. The researchers gathered data from various literature and randomly surveyed over 400 college students, used a systematic review approach, Chi-squared test, and descriptive statistics to review the evidence, and analyzed the survey data using the Statistic Package for Social Science (SPSS). In addition, the study explores the opportunity for compensating student-athletes and investigates the salaries of “celebrity” coaches and the minimal financial compensation or stipend student-athletes receive while playing for these coaches. The current study found that college and university sports leaders should not view student-athletes as mere athletes but as valuable assets that create organic growth for their college athletics and the NCAA benefits from endorsement and advertising deals. The result indicated that athletes should be able to earn extra money that raises their living standards above the poverty line, while college sports generate billions of dollars for universities, broadcasters, and sponsors. University coaches are signing multi-million-dollar contracts while their players are forced to live off $12,000 on average, and most of the money goes toward their tuition, room, books, board, and class needs. The study supports that the Supreme Court recently allowed colleges to provide “education-related” payments to student-athletes. The decision permits student-athletes to pursue endorsement deals based on their name, image, and likeness.